Disentangling the impacts of macroalgae on corals via effects on their microbiomes - Clements, Cody S.; Hay, Mark E. (Frontiers in Ecology and Evolution, 2023)
Tropical reefs are commonly transitioning from coral to macroalgal dominance, but the role of macroalgae in coral decline remains inadequately understood. A growing body of research suggests that algae may harm corals via disruptions to the homeostasis of the coral holobiont, including resident microbial communities, but the processes that mediate these potential microbial effects and the spatial scales at which they operate are uncertain. Resolving the relative importance and context dependencies of microbially-mediated algal-coral competition is critical for understanding and predicting coral dynamics as reefs further degrade. In this review, we examine the current state of knowledge surrounding algal impacts on corals via disruption of their microbiomes, with a particular focus on the mechanisms hypothesized to mediate microbial effects, the scales at which they are thought to operate, and the evidence from laboratory- and field-based studies for their existence and ecological relevance in the wild. Lastly, we highlight challenges for further advancing the field.